302 Is Age Just A Number in Cardiac Surgery? Evaluating Outcomes of An Octogenarian Cohort at A Single Cardiac Centre. (4th May 2021) - Argyriou, A; Hasan, R; Abunasra, H; McLaughlin, K; Bilal, H; Sogliani, F; Datta, S
Abstract: Introduction: Cardiac surgery in octogenarians contains many age-specific perioperative risk factors and outcomes yet to be fully understood. Method: All adults (N = 4957) undergoing cardiac surgery between 2011-2017 at our institution were retrospectively studied, encompassing 312 octogenarians. Data was evaluated with univariate and multivariate testing and mortality with Kaplan-Meier and cox-regression analyses. Results: Compared to septuagenarians, octogenarians revealed more patients having previous surgery (p = 0.016), less diabetic patients (p = 0.034), lower BMI (0.002), and longer hospital stay (p < 0.000). Compared to rest of study, octogenarians contained more females (p = 0.012), a greater Euroscore (p < 0.000), spent longer in ITU (p = 0.001) and contained more ITU readmissions (p = 0.023). The octogenarians did not contain significant 30- and 90-day mortality but revealed significant mortality at 1-year versus septuagenarians (p = 0.039) and rest of study (p = 0.001). Variables testing significant in a multivariate regression were inserted into a cox-regression that found octogenarian group-membership to be insignificant (p = 0.051) in a 12-covariate model. Independent risk factors for mortality included emergency surgery (p = 0.04), reoperation (p < 0.000), cardiac procedure (p = 0.007), ITU time (p = 0.041) and diabetes (p = 0.023). Conclusions: We report specific differences for octogenarians in perioperative characteristics along with promising short- and medium-term survival. Such outcomes must constantly be monitored so that cardiac surgery can be further tailored to this elderly cohort.